2003
DOI: 10.1002/mawe.200300707
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐porous Alumina Coatings for Improved Bone Implant Interfaces

Abstract: A new method is proposed for coating implants that produces a metal implant covered in a layer of nano-porous alumina ceramic. These layers are produced by first depositing a layer of aluminium on the implant surface and then anodising it in phosphoric acid to produce the nano-porous structure. This process results in the conversion of the aluminium to alumina containing 6-8wt% phosphate ions. The surface alumina layer is bonded to the substrate via an interfacial layer of fully dense anodised titanium oxide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 30 publications
1
33
0
1
Order By: Relevance
“…The main benefit of selective etching when compared to other existing processes to produce nanoporous alumina on implants, such as for instance anodization [28,72], is that the layer obtained is not a coating. There is no interface with the bulk, which is highly beneficial in terms of reliability since it avoids any problem related to lack of adhesion or delamination.…”
Section: Discussionmentioning
confidence: 99%
“…The main benefit of selective etching when compared to other existing processes to produce nanoporous alumina on implants, such as for instance anodization [28,72], is that the layer obtained is not a coating. There is no interface with the bulk, which is highly beneficial in terms of reliability since it avoids any problem related to lack of adhesion or delamination.…”
Section: Discussionmentioning
confidence: 99%
“…An electrochemical biosensor for the determination of blood glucose was constructed by the condensation polymerization of dimethyldichlorosilane at the surface of a porous alumina membrane [658]. Anodic porous alumina films can also be used as implants with enhanced bonebonding performance, by filling the nanopores with a bioactive material that supports normal osteoblastic activity [659]. …”
Section: 57mentioning
confidence: 99%
“…evaluation of the intrinsic nature of an uncoated porous alumina surface and with substrates configured in a manner that is conducive to subsequently forming an electrode such as closed conductive substrate rather than membrane (Prasad and Quijano 2006;Wolfrum et al 2006). Others have evaluated nonneuronal cell types on porous alumina, in particular osteoblasts, and shown good biocompatibility (Walpole et al 2003;Leary Swan et al 2005;Hoess et al 2007;Karlsson et al 2004). The objectives of our experiments were therefore to, firstly, evaluate the biocompatibility with neuronal cells of porous alumina configured in a manner compatible with CMOS processing and, secondly, to characterise adhesion versus alumina pore pitch.…”
Section: Introductionmentioning
confidence: 96%
“…Aluminium has also been associated with the pathogeny of Alzheimer's Disease, but a causal relationship has not been demonstrated (Perl and Moalem 2006). However, due to these concerns, Walpole et al (2003) and tested nano-porous alumina substrates for aluminium ion leakage and they concluded that the dissolution of ions into the culture was not toxic.…”
Section: Introductionmentioning
confidence: 97%